Efeito dos parâmetros biométricos e da altitude em estimativas da biomassa de raízes grossas de árvores em florestas do ecótono norte da Amazônia brasileira - Ramírez Narváez, Perla Natalia (2017)
Root biomass (belowground and aerial) of the different Amazonian forest types are estimated with a high degree of uncertainty in the evaluations carried out by the Brazilian National Inventory on Sources and Carbon Reservoirs. Improving these estimates results in a refinement of the understanding the mitigating role that Amazonian forests have face to the climate change. The aim of the study was to estimate the coarse-root biomass of trees located in ecotone forests of the northern Brazilian Amazonia, considering the effect of the biometric parameters of each individual (DAP = diameter of the breast height, H = total height) and its position in the altitudinal gradient. In this sense, 65 trees were sampled (DAP ≥ 10 cm, roots exposed and known mortality history) along 60 km of trails which crossing a PPBio (Brazilian Program for Biodiversity Research) research grid located in Maracá Ecological Station, Roraima. The biomass of the coarse roots of each sampled tree was considered as the sum of three components: all belowground root pieces (segment) with diameter ≥ 20 mm, buttress roots (aboveground roots) and stem base (base of the stem just below to the superficial soil line). These three compositional units were indirectly estimated associating their volume with the specific gravity of branches (buttress roots and stem base) and roots (belowground root). Data analysis was performed using linear and non-linear regression models. A t test was used to compare the means between dominant forest types. The coarse root biomass was positively related to the DBH of both forest types: ombrophilous (Y = 0.0011× X1.7206 ; n = 33; R2 =0.7855) and seasonal (Y = 0.0016 × X1.5742; n = 32; R2 = 0.7061). The relation between coarse roots biomassa and total height was partially explained taking into account the total number of sampled individuals, independent of the forest type (Y = 0.0004 × X2.2512; n = 65; R2 = 0.4858). Variation in the altitudinal gradient did not define distinctions the root biomass between individuals sampled. The mean of total coarse root biomass of ombrophilous forests (117.9 ±34.1 Mg ha-1) did not differ significantly from seasonal forests (118.9 ± 39.7 Mg ha-1). The mean of root:shoot ratio of ombrophilous forests (0.53 ± 0.13) was higher (t = 4.7314, p <0.0000) than that calculated for seasonal forest (0.41 ± 0.14). The conclusions of the study indicate that DBH is a good predictor of root biomass, because it has better explanatory power in relation to the total height of the trees and its position in the altitudinal gradient. With these results are expected improvements in the Brazilian estimates in relation to root biomass of different forest types in the Amazon.